Case report: Rare lung disease of infancy diagnosed with the assistance of a home pulse oximetry baby monitor - Yang, Kevin H.; Kulatti, Art; Sherer, Kimberly; Rao, Aparna; Cernelc-Kohan, Mateja (Frontiers in Pediatrics, 2022)
Neuroendocrine cell hyperplasia of infancy (NEHI) is a rare childhood interstitial lung disease characterized by a gradual onset of tachypnea, hypoxemia, and failure to thrive in the first two years of life. NEHI is challenging to diagnose and can masquerade as common respiratory infections and reactive airway disease. Timely diagnosis is essential to optimize management of comorbidities, improve outcomes, and prevent unnecessary interventions. We report a case of a 14-month-old male who was hospitalized multiple times with recurrent episodes of presumed bronchiolitis. However, early on, the parents had detected unexplained nighttime hypoxemia with a wearable home pulse oximetry baby monitor. While recurrent respiratory infections are common in infancy, our patient had numerous persistent symptoms refractory to traditional treatments, which prompted further workup and ultimately led to the diagnosis of NEHI. The home baby monitor provided useful information that accelerated workup for a presentation that did not fit the usual picture of recurrent bronchiolitis, bronchospasm, or pneumonia. These devices that monitor infant cardiopulmonary status and oxygenation are becoming increasingly popular for home use. There is controversy over their clinical utility due to the frequency of false alarms, excessive parental reliance on these devices, and lack of FDA oversight to ensure accuracy and effectiveness of these devices. Our case provides an example of how in certain clinical settings, information from these devices might serve as a complementary tool in the pediatrician’s medical decision-making and possibly lead to a rare diagnosis such as NEHI.